DEVELOPMENT OF TRAINING FOR THE POSITION OF REGISTRARS IN THE SUPREME COURT - ridwan, moch (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2021)
The registrar's position within the Supreme Court is a career position with the status of a Civil Servant, who is specifically tasked with regional and central courts to receive, examine, adjudicate and settle registered cases. The clerk of the court who serves in the Court has an important role in handling the administration of the trial and the execution of the judge's decision in the Court. This role further clarifies the position and orientation of the function of the part of justice services for citizens optimally. This study aims to develop an education and training policy plan that supports the profession of court officials before carrying out their duties and functions as Registrars.This study uses a qualitative method with a normative juridical approach in the field of education and training. The results of this study found that the current administration of education and training for registrars, such as curriculum content and learning time is still lacking as a basis for competencies and specifications for job career paths required by the organization. This needs to be adjusted to the needs of the organization in meeting the professional standards of the clerkship position within the Supreme Court.